Clinicicopathologic Profile of Patients Presentaing with Abdominal Tuberculosis in a Tertiary Care Hospital. - Anwar, Ejaz; Ali, Zafar; Alam, Intekhab (Journal of Postgraduate Medical Institute, 2011)
To evaluate pattern of presentation of patients with abdominal tuberculosis (TB) in a tertiary care hosptial. This was a hosptial based non interventional descriptive case series study. It included patients of both sexes, more than 12 years of age, with clinically suspected abdominal tuberculosis. the study was carried out in medical ward of LRH, peshawar from January to December 2003. Patients were selected by non probability conventient sampling method after obtaining an informed consent. Intestinal tuberculosis was the cmost common entitiy in patietns with TB abdomen. the most frequent presenting features of abdominal TB were fever and abdominal pain. CT abdomen had the highest diagnostic yeild.